Oogenesis in summer females of the rice water weevil, Lissorhoptrus oryzophilus Kuschel (Coleoptera: Curculionidae), in southern Zhejiang, China - Shi, Sheng-wei (Zhejiang University Press, 2007)

(untitled)
The rice water weevil, Lissorhoptrus oryzophilus Kuschel, has two generations in southern Zhejiang, China. To determine oogenesis in first-generation females (summer females) and its relations to temperature, females were collected from a rice field in early and mid-July and reared on young rice plants at 28, 31 and 34 °C in the laboratory. Percentage of females having oocytes, number of oocytes of different stages (stage-I, from early previtellogenesis to middle vitellogenesis; stage-II, late vitellogenesis; and mature-oocyte stage), and length of ovarioles were determined every 10 d of feeding. At each temperature, oogenesis took place in over 40% of females after 20~40 d of feeding, but only 0.0~3.3 stage-I, 0.0~0.8 stage-II and 0.0~1.1 mature oocytes were observed at each observation date. Temperature had significant effect on number of stage-I oocytes but not on number of stage-II and mature oocytes in early July females; temperature had no significant effect on number of oocytes of either stage in mid-July females. Conclusively, in southern Zhejiang, summer L. oryzophilus females have great potential to become reproductive on rice, but their oogenesis activity is very low, with the overall procedures little affected by temperature.